2022
DOI: 10.1186/s13034-022-00532-4
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization, depression, and non-suicidal self-injury among Chinese adolescents: the moderating role of the 5-HTR2A gene rs6313 polymorphism

Abstract: Background Peer victimization is a crucial risk predictor for adolescent non-suicidal self-injury (NSSI). However, adolescent NSSI reactions to peer victimization exhibit large individual differences. This study explored whether depression mediated the association between peer victimization and adolescent NSSI, and whether this mediating path was moderated by the 5-HTR2A gene rs6313 polymorphism. Methods A total of 667 adolescents (Meanage = 12.81,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In addition, the results of the mediating effect analysis indicated that depression mediated the relationship between cumulative ecological risk and NSSI in adolescents, consistent with previous research findings on different ecological risk (Li et al, 2022;Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, the results of the mediating effect analysis indicated that depression mediated the relationship between cumulative ecological risk and NSSI in adolescents, consistent with previous research findings on different ecological risk (Li et al, 2022;Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the results of the mediating effect analysis indicated that depression mediated the relationship between cumulative ecological risk and NSSI in adolescents, consistent with previous research findings on different ecological risk (Li et al, 2022; Wei et al, 2021). The results proposed that cumulative ecological risk led to an increase in adolescent depression and further led to the occurrence of adolescent NSSI.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is worth noting that after experiencing peer victimization, some individuals have more severe self‐injurious behavior (Li et al, 2022; Wang & Liu, 2019), indicating that moderators could exist. Improving the understanding of the underlying processes of NSSI and moderating factors is vital to inform the design of prevention, early intervention, and treatment programs for adolescents at risk of these behaviors.…”
Section: Introductionmentioning
confidence: 99%